2015
DOI: 10.1158/1055-9965.epi-15-0388
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Predicts Progression of Human Gastric Lesions

Abstract: Background Development of the intestinal subtype of gastric adenocarcinoma is marked by a progression of histopathological lesions. Residents of the Andean regions of Colombia are at high risk for gastric cancer. Methods A cohort of 976 Colombian subjects was followed over 16 years examining effects of Helicobacter pylori eradication and treatment with anti-oxidants on progression of lesions. We performed methylation analysis of DNA from baseline antral biopsies from 104 subjects for whom follow-up data were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
6
19
0
1
Order By: Relevance
“…Moreover, the common trait of H. pylori strains that have increased risk of inducing gastric adenocarcinoma is the expression of specific virulence genes including the protein cytotoxin-associated gene A (CagA) [2] and the vacuolating cytotoxin A (VacA) [3] (Box1). Environmental components [4] and host factors [5] have been also shown to be involved in the outcome of H. pylori infection. But, whether host and pathogen genomic variations in a spatio-temporal axis are associated with the development of gastric diseases, overall the clinical outcome of H. pylori infection-induced gastric carcinogenesis is determined by the progression along the histologic cascade from non-atrophic gastritis to adenocarcinoma [6].…”
Section: Infection With Helicobacter Pylorimentioning
confidence: 99%
“…Moreover, the common trait of H. pylori strains that have increased risk of inducing gastric adenocarcinoma is the expression of specific virulence genes including the protein cytotoxin-associated gene A (CagA) [2] and the vacuolating cytotoxin A (VacA) [3] (Box1). Environmental components [4] and host factors [5] have been also shown to be involved in the outcome of H. pylori infection. But, whether host and pathogen genomic variations in a spatio-temporal axis are associated with the development of gastric diseases, overall the clinical outcome of H. pylori infection-induced gastric carcinogenesis is determined by the progression along the histologic cascade from non-atrophic gastritis to adenocarcinoma [6].…”
Section: Infection With Helicobacter Pylorimentioning
confidence: 99%
“…In the replication cohort and methylation group, for 104 subjects for whom single colony cultures were not available, the vacA s region was characterized from biopsy DNA as previously described (Schneider et al 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Many changes in DNA methylation occur non-specifically, as a function of aging or environmental factors (Teschendorff et al 2010). Some changes may occur in premalignant lesions, making methylation changes potentially useful as biomarkers of gastric cancer risk (Schneider et al 2015; Watanabe et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…At same period, a cross-sectional study that also conducted by Asada and Shimazu suggested that NKX6.1 methylation level is closely associated with the risk of gastric cancer incidence [82] . At almost same period, Schneider held a cohort for over 16 years in Colombia, claimed that the level of NKX6.1 DNA methylation was associated with gastric cancer progression, further illustrates that epigenetic modification may affect NKX6.1 expression level in tumor [83] . From the studies we mentioned before, NKX6.1 may be involved in the development of WDNETs, HCC, or gastric cancer, whereas more functional experiments in vivo and vitro are required to confirm the theoretical hypothesis.…”
Section: Nkx61mentioning
confidence: 99%